Biological Mechanism of Orthodontic Movement in The Treatment of Skeletal Class II Malocclusion Using Twin Block: English - Hilda Fitria Lubis; Erik Idrus; Dewi Fatma Suniarti Sastradipura; Retno Widayati; Miesje Karmiati Purwanegara (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Patients of growing age with dentoskeletal class II malocclusion are often found in the clinic, to avoid further severity it is recommended to use functional appliance in cases involving skeletal. Review: Functional appliances have been widely used since activators were introduced by Andersen, but the use of activators has many disadvantages such as the shape that blends between the maxilla and mandible making it difficult for patients to open their mouths, speak and eat, then the large shape makes patients uncomfortable and causes facial changes. Clark developed the twin block to answer the previous shortcomings, which is a simple and separate design between the mandible and maxilla causing patients to be more comfortable in speaking and eating so that it is comfortable to use for a long time. Twin block is a functional appliance used to reposition the mandible forward in cases of class II malocclusion with retrognathic mandible. Conclusion: This paper describes the design and use of twin block and its effectiveness in skeletal correction. In addition, its use was found to improve facial shape, reduce overjet and overbite, corrected molar relationships and alleviated patient complaints.